Constrained Choices: How Bosnian Communists Lost Their Party Before Losing the Elections - Muharemović Ensar (Comparative Southeast European Studies)
This article demonstrates that, during the year 1990, the process of democratization in Bosnia-Herzegovina was intentionally decelerated and stifled by the ruling Communist Party due to the ideological conservatism of its leadership. This process directly contributed to the party’s ultimate loss of power. Archival documentation, extensive newspaper coverage from this period, and testimonies of key participants are used to recreate the contextual circumstances under which the crucial events unfolded. The critical importance of strategic decisions made by the ruling political elites under extreme time pressure proved to be a key factor in determining their ability to retain power. The case of Bosnia-Herzegovina in 1990 demonstrates that slow, indecisive, and gradual policymaking during the transformational period from communism to democracy could have disastrous consequences for the electoral chances of the incumbent communist parties.